The Determinants of Student Test Scores: Academic, Family, and Learning Environment Factors a Multiple Linear Regression Analysis - Rena Nainggolan; Fenina Adline Twince Tobing (Universitas Multimedia Nusantara, 2026)
This study aims to analyze the influence of academic, family, and learning environment factors on student exam scores. The study employs a quantitative approach using secondary data in the form of the Student Performance Factors dateset comprising 6,607 observations. The dependent variable in this study is student exam scores (Exam_Score) [1], while the independent variables include study hours (Hours_Studied), attendance (Attendance), previous scores (Previous_Scores), tutoring sessions (Tutoring_Sessions), parental involvement (Parental_Involvement), and access to learning resources (Access_to_Resources) . The analytical techniques used were descriptive statistics and multiple linear regression. The results indicate that the regression model is statistically significant simultaneously with an F-value of 1,601 and p < 0.001, and explains 66.0% of the variation in students’ exam scores (R² = 0.660). Partially, study hours, attendance, previous scores, and tutoring sessions have a positive and significant effect on test scores. Additionally, students with higher levels of parental involvement and access to learning resources tend to achieve better test scores [2] . These findings indicate that students’ academic achievement is not solely determined by individual study effort but is also influenced by family support and the availability of an adequate learning environment.